Demokracja a religia w świetle klasycznych teorii umowy społecznej - Wandowicz, Konrad (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
In the author’s opinion we can agree that the theories of contractualism provide an excellent foundation for the legitimization of democracy. At the same time, he claims that democracy, and liberal democracy in particular, cannot be said to be the necessary outcome of social contract. Hobbes was the advocate of absolute monarchy, although his theory permiabsolute aristocracy as well as absolute democracy. Locke, a supporter of a limed monarchy, emphasized the principles of people’s sovereignty. Rousseau, an apologist for the l will, tended to support such the solon that it is not the people’s will but the wisest ones’ whichrulthe sciety as long as they have the people’s benefit in mind. Glorifying his general will, Roussau has become the founder of modern political totalitarianism. When discussing the relations between state and religion/church the above three classic speculators on the theory of social contract assumed the individual freedom of religious beliefs. Ultimately, it is the state though that regulates the external manifestations of faith, as it is the only political entity to arbitrate conflicts between individual interests, and express the pubgood, whatever that means.